Analysis of seasonal soil organic carbon content at bukit Jeriau forest, Fraser Hill, Pahang - Mohd Khairul Amri, Kamarudin; Ahmad Adnan, Mohamed; Sahibin, Abd. Rahim (Malaysian Society of Analytical Sciences, 2016)
Soil carbon is the carbon held within the soil, primarily in association with its organic content. The total soil organic carbon study was determined in a plot at Bukit Jeriau forest in Bukit Fraser, Pahang, Malaysia. The aim of this study is to determine the changing of soil organic carbon between wet season and dry season. Soil organic carbon was fined out using titrimetric determination. The soil organic carbon content in wet season is 223.24 t/ha while dry season is 217.90 t/ha. The soil pH range in wet season is between 4.32 to 4.45 and in dry season in 3.95 to 4.08 which is considered acidic. Correlation analysis showed that soil organic carbon value is influenced by pH value and climate. Correlation analysis between clay and soil organic carbon with depth showed positively significant differences and clay are very much influenced soil organic carbon content. Correlation analysis between electrical conductivity and soil organic carbon content showed negative significantly difference on wet season and positively significant different in dry season.